SuarAman Inovasi Platform Dukungan Psikologis Daring Berbasis Anonimitas bagi Mahasiswa Universitas Negeri Malang - Adinda Arofah Putri Indarti,; Abdul Aziz Tri Nugroho,; Alfia Nuraini,; Alfi Nur Hayati,; Aulia Nadia Majid,; Azzahra Rahmalia Putri,; Desta Awwallillah Zain,; Bilbinia Herlinda Kuncoro Putri, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
In the Indonesian higher education context, student psychological well-being is a critical concern, particularly post-pandemic. This quantitative study designed SuarAman, an anonymous online psychological support system for Universitas Negeri Malang students. Using a User-Centered Design approach with 50 participants, data revealed 74% demanded anonymous platforms, while 88% considered anonymity essential for mental health support. The anonymous "Peer Listener" chat feature was strongly preferred (92%), indicating a clear inclination toward informal peer support. With 66% very likely to adopt the platform, substantial user uptake is anticipated. Notably, half reported intermittent isolation and 48% faced frequent academic stress. SuarAman incorporates three core features: Online Peer Listener service, Student Community Forum, and Non-Formal Consultation Service. This initiative helps overcome stigma associated with traditional counseling. The findings emphasize the necessity of robust data security, comprehensive peer listener training, and diligent forum moderation in developing effective digital mental health solutions for university environments.